Factors affecting the sorption of trivalent chromium by zeolite synthesized from coal fly ash - Sui, Yanming; Wu, Deyi; Zhang, Dalei; Zheng, Xiangyong; Hu, Zhanbo; Kong, Hainan (Journal of colloid and interface science, 2008)
This research was initiated to determine the effects of different constituents and properties of zeolite synthesized from fly ash (ZFA) on Cr(III) sorption. The uptake of Cr(III) by ZFA was influenced greatly by pH, increasing with the increase in pH. The pH was controlled mainly by calcium-related components (especially CaCO 3 and free CaO) and zeolite components in ZFAs. Sorption maximum of Cr(III) ( Q m ), determined by a repeated batch equilibration method, ranged from 22.29 to 99.91 mg/g for the 14 ZFAs. The Q m value correlated significantly with Ca-related components. The correlation coefficients were 0.9467, 0.5469, 0.7521, and 0.9195 for total Ca, CaCO 3, CaSO 4, and f.CaO, respectively. The Q m value was also closely related to cation-exchange capacity ( r = 0.6872 ) and specific surface area ( r = 0.7249 ). Correlation coefficients of Q m with dissociated Fe 2O 3 and Al 2O 3 were much higher than those of total Fe and total Al contents, respectively. It was suggested that, in ZFAs, zeolite and iron oxide acted as ion exchanger and adsorbent for Cr(III), respectively, while Ca components elevated the pH of the reaction system and consequently promoted ion exchange and adsorption and caused the surface precipitation of chromium hydroxide. Both the zeolite component and the nonzeolite component in zeolites synthesized from fly ashes contributed to sorption of Cr(III). The figure shows that the calcium component could increase pH and thus enhance sorption.